The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.15740/has/ijas/11.1/45-49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crop geometry, drip irrigation and bio-regulator on growth, yield and water use efficiency of wheat (Triticum aestivum L.)

Abstract: A field experiment was conducted during Rabi season, 2011-12 at Niche Area Excellence Farm, Bikaner to study the effect of crop geometry, drip irrigation and bio-regulator on growth, water use efficiency and yield of wheat (Triticum aestivum L.). The experiment was conducted in Randomized Block Design with three irrigation schedules viz., 60, 80 and 100 per cent ETc, two crop geometry levels viz., 22cm paired row spacing-4 rows (120 cm lateral spacing) and 22 cm normal spacing sowing (60 cm lateral spacing) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Irrigating the wheat crop as soon as the SWC reaches 35 mm has been proven as an optimal irrigation scheduling treatment to gain better grain yield, which is mainly due to greater yield components (especially number of grains per spike) and HI values under this specific treatment during the two growing seasons. This result corroborates well with the findings of Bhunia et al [39], which showed that yield attributes like spike length, grain weight and number of grains per spike increased at optimum soil moisture rather than higher irrigation. Bandyopadhyay et al [40] also stated that moderate deficit irrigation might increase the root growth and facilitate remobilization of reserve carbon to grains and accelerate grain filling, which could be responsible for improved grain yield under moderate deficit irrigation (SWC = 35 mm) as observed in our study.…”
Section: Effects Of Isl and Nam On Grain Yieldsupporting
confidence: 92%
“…Irrigating the wheat crop as soon as the SWC reaches 35 mm has been proven as an optimal irrigation scheduling treatment to gain better grain yield, which is mainly due to greater yield components (especially number of grains per spike) and HI values under this specific treatment during the two growing seasons. This result corroborates well with the findings of Bhunia et al [39], which showed that yield attributes like spike length, grain weight and number of grains per spike increased at optimum soil moisture rather than higher irrigation. Bandyopadhyay et al [40] also stated that moderate deficit irrigation might increase the root growth and facilitate remobilization of reserve carbon to grains and accelerate grain filling, which could be responsible for improved grain yield under moderate deficit irrigation (SWC = 35 mm) as observed in our study.…”
Section: Effects Of Isl and Nam On Grain Yieldsupporting
confidence: 92%
“…Drip irrigation is regarded as one of the most efficient irrigation technologies in terms of water, energy, and fertilizer use [13,14]. Drip irrigation transports water and fertilizer to crops directly [15,16] and provides a suitable soil environment for crops. However, research on the application of drip irrigation in summer maize in North China is currently limited due to the traditional conception that summer maize does not require watering in North China [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The distance between adjacent rows in the strip of tilled soil is smaller, and between the rows in successive strips separated by the strip of untilled soil is greater [18,19]. However, compared to traditional row sowing, paired-row sowing changes plants and canopy parameters [20,21]. Changing the row spacing while maintaining the same sowing density requires a change in the distance between plants in a row.…”
Section: Introductionmentioning
confidence: 99%